Morphological differences between Bahasa Melayu and English: Constraints in students’ understanding - Mat Awal, Norsimah; Abu Bakar, Kesumawati; Abdul Hamid, Nor Zakiah; Jalaluddin, Nor Hashimah (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
Teaching English language is a big challenge in Malaysia. Students are still unable to master or even comprehend the language even after eleven years learning the language at the primary and secondary levels. A study conducted on three hundred and fifteen Form Two students show that one of the most obvious weaknesses of the students lies in the morphological aspect of the language. Affixes, adverbs, adjectives, plural forms are some of the categories that students find problem with. Findings of the study show that over 60% of the mistakes detected can be categorized as morphological. This can be attributed to the different morphological structures between Bahasa Melayu and English, for example the -ly suffix for adverbs, superlative form for adjectives, -s, -es markers for plurality and reflexive pronoun, and these are some of the constraints the students face in learning the English language. This paper will present a comparative linguistic analysis on the morphological structures of the two languages.